2012
DOI: 10.1038/ncomms2298
|View full text |Cite
|
Sign up to set email alerts
|

The developmental basis of bat wing muscle

Abstract: By acquiring wings, bats are the only mammalian lineage to have achieved flight. To be capable of powered flight, they have unique muscles associated with their wing. However, the developmental origins of bat wing muscles, and the underlying molecular and cellular mechanisms are unknown. Here we report, first, that the wing muscles are derived from multiple myogenic sources with different embryonic origins, and second, that there is a spatiotemporal correlation between the outgrowth of wing membranes and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…Musculus occipitopollicalis is specific to chiropterans being probably derived from the m. platysmа as is shown by its innervation by the nervus facialis (Tokita et al 2012); note that the same innervation is found in the propatagial muscle of colugos (Thewissen and Babcock 1993), which we call the m. tensor propatagii. The m. occipitopollicalis of chiropterans originates from the midline of the supraoccipitale or, in Pteropus (Humphry 1869), by four strands: from the occipital crest, lower jaw, throat, and the m. pectoralis.…”
Section: Musculature Of Wing Membranementioning
confidence: 66%
See 3 more Smart Citations
“…Musculus occipitopollicalis is specific to chiropterans being probably derived from the m. platysmа as is shown by its innervation by the nervus facialis (Tokita et al 2012); note that the same innervation is found in the propatagial muscle of colugos (Thewissen and Babcock 1993), which we call the m. tensor propatagii. The m. occipitopollicalis of chiropterans originates from the midline of the supraoccipitale or, in Pteropus (Humphry 1869), by four strands: from the occipital crest, lower jaw, throat, and the m. pectoralis.…”
Section: Musculature Of Wing Membranementioning
confidence: 66%
“…In giving this name, Strickler followed Macalister (1872), who had properly defined its homology but described it untenably (in Megaderma, both Macalister and Strickler gave the same name to a slip of the m. latissimus dorsi in spite of its dorsal course relative to the brachial plexus). This muscle is also mentioned as the m. cutaneus maximus in the embryological research of Carollia (Tokita et al 2012). We did not find it in the fruit bats or in horseshoe bats; probably we lost this extremely thin fascicle removing the skin.…”
Section: Musculature Originating From Trunkmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the recent descriptions of staging systems or developmental series in mammals are those of some bats (Cretekos et al 2005;Tokita 2006;Wang et al 2010), tenrecs (Werneburg et al 2013a), and the echidna (Werneburg and Sánchez-Villagra 2011). These studies have been stimulated not only by the experimental approaches to understand evolutionary novelties arising in development and involving molecular biology (e.g., Sears 2011;Tokita et al 2012;Montandon et al 2014). The establishment of quantitative methods to compare developmental timing among species (e.g., Smith 2001; Germain and Laurin 2009;Maxwell and Harrison 2009;Goswami et al 2016) has also stimulated analyses of accumulated knowledge, revisions of the anatomy of model species previously undocumented (Hautier et al 2013;Werneburg et al 2013b), and new studies on the comparative embryology and perinatal life of mammals (Bininda-Emonds et al 2003), as in our research which was the basis of the animation presented here (Werneburg et al 2016).…”
Section: Integrating Traditional Embryology With Modern Analytical Tementioning
confidence: 99%